2018
DOI: 10.1002/sd.1910
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable development and architectural practice: Framing strategic approaches in the United Kingdom

Abstract: The concept of sustainability is widely accepted in the design of the built environment; however, in architectural practice, there exist multiple, often competing, interpretations and agendas. This research analyses this variety and develops a unique framework that reveals actual and potential paths for sustainable design. In-depth interviews were conducted with 24 high-profile sustainable architecture practices in the United Kingdom. The data reveal a range of sustainable practice, which is grouped into consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The global energy and electricity consumption in the Global Energy Review 2020 has been greatly reduced, but the construction industry is still not a small load on the global environment [16]. In the sustainable construction topic, global construction researchers have proposed various solutions, including the use of minimal impact materials, the use of natural materials, and recycling as much as possible [17]. Due to the current global population growth trend, the construction industry consumes a lot of resources and energy, and this situation is expected to worsen in the near future [16].…”
Section: Sustainable Buildingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The global energy and electricity consumption in the Global Energy Review 2020 has been greatly reduced, but the construction industry is still not a small load on the global environment [16]. In the sustainable construction topic, global construction researchers have proposed various solutions, including the use of minimal impact materials, the use of natural materials, and recycling as much as possible [17]. Due to the current global population growth trend, the construction industry consumes a lot of resources and energy, and this situation is expected to worsen in the near future [16].…”
Section: Sustainable Buildingsmentioning
confidence: 99%
“…Based on the above literature evaluation scope and content analysis, it was found that most evaluation tools cover issues such as the internal environment of the building, the area of the building base, and the surrounding environment of the building [45,47]. The purpose of this study is to further generalize and construct a sustainable campus ecological building index that is suitable for Taiwan's geographical characteristics and has a sustainable conceptual framework such as environmental, social, and economic aspects [17,45]. Taiwan is located on the southeast coast of the Asian continent and on the west coast of the Pacific Ocean, between Japan and the Philippines, and is located in the center of the East Asian island arc.…”
Section: Sustainable Architecture Evaluationmentioning
confidence: 99%
“…The dense forests that were prevalent at the time were ample sources of material. The oldest techniques of weaving and molding walls were gradually replaced by timber building using clayed straw (non-flammable thatch), as roofing or the technique of erecting walls based on filling timber frames with straw wrapped around wooden planks and covered with clay from both sides (15) stages of the investment, from the design stage, through delivery, to maintenance and service (18).…”
Section: Straw As a Building Materialsmentioning
confidence: 99%